Positive Rate of Human Papillomavirus and Its Trend in Head and Neck Cancer in South Korea - Jun, Hyun Woong; Ji, Yong Bae; Song, Chang Myeon; Myung, Jae Kyung; Park, Hae Jin; Tae, Kyung (Frontiers in Surgery, 2022)
Introduction: This study aimed to investigate the positive rate of human papillomavirus (HPV) and its trend in head and neck squamous cell carcinoma (HNSCC) in South Korea and to evaluate the clinical differences between HPV-positive and -negative tumors. Methods: We studied 300 patients with HNSCC arising in the oropharynx (n=77), oral cavity (n=65), larynx (n=106), hypopharynx (n=40), and sinonasal cavity (n=12), treated in a tertiary university hospital in South Korea from January 2008 to July 2020. HPV status was determined using p16 immunohistochemical staining of formalin-fixed paraffin-embedded tissues. Results: Of the 300 patients with HNSCC, the positive rate of p16 was 30.3% (91/300). The p16 positive rate was 70.1%, 13.9%, 20.8%, 15%, and 0% in the oropharynx, oral cavity, larynx, hypopharynx, and sinonasal cavity, respectively. HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) patients were significantly younger than HPV-negative OPSCC patients. The positive rate of HPV in OPSCC has increased over time from 2008 to 2020, but has not changed significantly in the other primary sites. The disease-free survival curve of HPV-positive OPSCC was significantly better than that of HPV-negative tumors. Conclusion: The positive rate of HPV in Korean patients with OPSCC is significantly high (70.1%), similar to that in North America and Europe, and has increased abruptly in the past 12 years.